Aswaja Local Content Curriculum Management in Forming the Character of Students in Madrasah Aliyah Nu Indramayu - Masduki Masduki; Alvin Maulana Al Bahri (Universitas Negeri Semarang, 2024)
The moral and ethical crisis in Indonesia, as well as the rising crime rates, highlight the importance of character education. The implementation of the Aswaja-based local curriculum at Madrasah Aliyah NU Indramayu focuses on ethical and moral values, aiming to build students' character. This study aims to examine the management of the local curriculum at the school, covering the planning, implementation, and evaluation stages. In the planning phase, the school establishes the subjects, appoints teachers, and allocates resources. Implementation includes reviewing the syllabus, preparing lesson plans, and conducting assessments. However, challenges such as frequent changes in teaching staff and limited innovation by the school principal in developing teaching methods have been identified. Additionally, the supervision of the curriculum's implementation is not optimal. Despite these issues, the application of Aswaja's local wisdom values is expected to address the nation's moral crisis effectively.